Disease-Related Predictors of Health-Related Quality of Life in Youth With Eosinophilic Esophagitis. (12th October 2017) - Lynch, Mary K; Barnes, Margaux J; Dimmitt, Reed A; Martin, Lisa; Rothenberg, Marc E; Goodin, Burel R
Abstract: Objective: To evaluate relations between health-related quality of life (HRQoL) and clinical symptom presentation in youth with eosinophilic esophagitis (EoE). We hypothesized that presence of dysphagia, reflux, nausea/vomiting, and epigastric pain would be related to poorer HRQoL. In predictive models, it was hypothesized that dysphagia, reflux, nausea/vomiting, and epigastric pain would each significantly and uniquely predict poorer HRQoL. Methods: This cross-sectional, two-study design included 91 dyads comprised children with EoE and their respective caregivers across two tertiary children's hospitals, Site 1 in the Midwest ( N  = 47) and Site 2 in the Deep South ( N  = 44). Youth and their caregivers both completed questionnaires addressing HRQoL and EoE symptoms during clinic visits. Results: Per youth self-report, epigastric pain was found to be a significant predictor of poor physical and psychosocial HRQoL. Per caregiver-proxy reports, epigastric pain was found to be a significant predictor of poor physical HRQoL. Conclusions: The clinical symptoms of EoE, specifically epigastric pain, were found to be predictive of the youth's HRQoL. Targeted interventions to help youth with EoE better manage their specific symptom experiences could ultimately improve HRQoL.